A voz das domésticas: o que dizem e as maneiras de dizer em um sindicato - Garcia, Ana Laura Gonçalves (2020)
This study seeks to contribute to the analysis of famele speech discurses. It is a proposal aimed at understanding the voice of domestic workers and their representatives in The Union of Domestic Workes of Ribeirão Preto. Based on the Analysis of the French Discurses, under the guiance of the studeis of Michel Foucault and Michel Pêcheux, this work can apreehed discursies that materialized in the speech about a work performed, mostely, by woman and historicaly unequal in rights. The object of this research was carried out using an audio e video recording of workers statments but also their representative and his lawyer at the Union of Domestic Workes of Ribeirão Preto. The analysis proposed by this reserch seeks answer to the following questions: what do the domestic workes say in the meetins of indication? Your ways wrong or not in relation to the speech of the members presente at the meeting? What are the language resousers used by them? The survery and analysis of the data should creat an understanding of how a series of historycal and social representetion is respected in domestic work. It will also be possible to apreehed the uses of languege in the internal public space, or to indicate what the objective should be the defenses of rights. In addition, we can identify which are the discursive marks that materialize as precarius conditions of this category of work. Finally, based on our analysis of these speeches we can desmontrate that, when necessary, employment and daily life are not affected by workers and the negative frequency of such symbolic capacity, these workers khow how to speak and use or say.